2017
DOI: 10.1016/j.neuron.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 Accelerates Early Seeding of Amyloid Pathology

Abstract: SUMMARY Accumulation and aggregation of amyloid-β (Aβ) in the brain is an initiating step in the pathogenesis of Alzheimer’s disease (AD). The ε4 allele of apolipoprotein E (apoE) gene is the strongest genetic risk factor for late-onset AD. Although there is strong evidence showing that apoE4 enhances amyloid pathology, it is not clear what is the critical stage(s) during amyloid development apoE4 has the strongest impact. Using apoE inducible mouse models, we show that increased expression of astrocytic apoE4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
266
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(275 citation statements)
references
References 42 publications
8
266
0
1
Order By: Relevance
“…Recombinant E4 has been reported to increase Aß production by receptor-mediated effects, 63 and in transgenic mouse models, E4 promotes the seeding of amyloid plaques. 4,5,63 Aß can in turn induce tau phosphorylation via GSK3ß activation. 64 In our neuronal cultures, genetic correction of E4 did not increase APP expression, Aß42/Aß40 ratio, or GSK3ß phosphoactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant E4 has been reported to increase Aß production by receptor-mediated effects, 63 and in transgenic mouse models, E4 promotes the seeding of amyloid plaques. 4,5,63 Aß can in turn induce tau phosphorylation via GSK3ß activation. 64 In our neuronal cultures, genetic correction of E4 did not increase APP expression, Aß42/Aß40 ratio, or GSK3ß phosphoactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence suggest that ApoE4 risk in AD principally relates to enhanced and accelerated cerebral Aβ pathology [4]. More precisely, ApoE4 appears to accelerate the early seeding of amyloid pathology, most likely by decreasing Aβ clearance and enhancing Aβ aggregation [5]. Shi et al .…”
Section: Characteristics Of Patients With Frontotemporal Dementia (Ftmentioning
confidence: 99%
“…Multiple lines of evidence suggest that ApoE4 risk in AD principally relates to enhanced and accelerated cerebral Ab pathology [4]. More precisely, ApoE4 appears to accelerate the early seeding of amyloid pathology, most likely by decreasing Ab clearance and enhancing Ab aggregation [5]. Shi et al recently described how ApoE4 increases the burden of cerebral tau pathology, neuroinflammation, and brain atrophy in a P301S mouse model of frontotemporal dementia (FTD) and in vitro; they also demonstrated that in patients with a primary tauopathy, ApoE4 was associated with more severe regional neurodegeneration and that ApoE41 AD patients with amyloid-b (Ab) pathology showed faster disease progression [6].…”
mentioning
confidence: 99%
“…ApoE functions as the main cholesterol carrier in the brain (Mahley, 1988), and the variant E4 increases the risk of developing AD (Corder et al, 1993). Aside from its role in fat metabolism, ApoE4 has been shown to speed up Aβ seeding (Bales et al, 1997;Liu et al, 2017) and mediate the clearance of Aβ peptide less efficiently than other ApoE variants (Castellano et al, 2011;Robert et al, 2017). Interestingly, mice carrying the ApoE4 variant show impaired endosomal-lysosomal pathways (Nuriel et al, 2017) and EV biogenesis (Peng et al, 2019).…”
Section: Genetic and Biological Evidence For A Role Of Degradativementioning
confidence: 99%
“…It is tempting to hypothesize that ILVs/exosomes may enhance the formation of Aβ fibers to trap undegraded cellular material accumulated in MVBs due to lysosomal dysfunction. Indeed, ApoE (ApoE4 isoform is the second highest risk factor for AD after aging) was shown to be required for amyloid plaque formation (Bales et al, 1997;Liu et al, 2017). Then amyloid fibers entangled with cellular waste would be secreted to the cellular space after the fusion of MVBs to the plasma membrane and cleared by microglia.…”
Section: Enhanced Secretion Of Exosomes May Trigger Increased Aβ Gementioning
confidence: 99%